Ultra‐Narrowband Photodetector with High Responsivity Enabled by Integrating Monolayer J‐Aggregate Organic Crystal with Graphene. Issue 17 (14th June 2021) - Sun, Beilei; Zhou, Guodong; Wang, Yi; Xu, Xin; Tao, Li; Zhao, Ni; Tsang, Hon Ki; Wang, Xinran; Chen, Zefeng; Xu, Jian‐Bin
Abstract: Narrowband photodetection has great significance for full‐color imaging and machine vision. The most common way to realize narrowband detection is to combine a bandpass filter with a broadband photodetector. Herein, an ultra‐narrow bandwidth photodetector without bandpass filter based on the combination of a monolayer J‐aggregate organic crystal with graphene is demonstrated. The monolayer PTCDI‐C13 J‐aggregate organic crystal grown on h‐BN substrate, which exhibits an absorption bandwidth of 10 nm, works as a light‐absorption material for narrowband photodetection; and graphene provides a conducting channel for photo‐induced carriers from the monolayer J‐aggregate film. Thanks to the ultra‐narrowband absorption of the monolayer PTCDI‐C13 J‐aggregate organic crystal and the high mobility of graphene, an ultra‐narrow spectral response of ≈13 nm and high responsivity of 1000 A W ‐1 can be achieved in photoconductor mode. This design concept is generic for other J‐aggregates with different absorption windows and provides a new method to fabricate highly responsive narrowband photodetector. Abstract : By combining monolayer J‐aggregate organic crystal with graphene, ultra‐narrowband photodetectors are designed and fabricated. Thanks to the ultra‐narrowband absorption of the monolayer PTCDI‐C13 J‐aggregate organic crystal and the high mobility of graphene, an ultra‐narrow spectral response of ≈13 nm and high responsivity of 1000 A W −1 can be achieved in photoconductor mode.